MT4 Bags / Nur Aishah Mat Thani - Mat Thani, Nur Aishah (2020)
The future looks promising for MT4 Bags in Banting, especially around Banting Town which is heading towards rapid development. There are already a number of commercial and luxury business shop developments in the surrounding area. The development of mixed shops that contradict what is being sold, sales revenue and the possibility that some already have customers nearby is also underway. we hope to meet the hopes and aspirations of developing the local apparel market and inspire young people to offer. In the planning of a team member of our sustainable production, continuity and efficiency at all expense, four guiding principles need to be developed to achieve our goals. It is important to take the following steps. With the increasingly growing developments and excitement of the world today, our company guarantees our commitment on handbag moding patterns on the sector as one of our goals is to overstate our business power. Although there are now more than five businesses offering the same business as us in Banting Town, only three of them offer online business and open for hiring agents or dropship to further expand our business empire here so that the whole of Malaysia even abroad can also feel wear or use the product we sell i.e. handbags.